Carotid artery ligation via sternotomy as a palliative surgery: Case report of advanced intramediastinal malignant soft tissue tumor. Issue 8 (2nd April 2021) - Eguchi, Kohtaro; Kobayashi, Kenya; Takano, Tomonari; Ito, Akiko; Sakai, Azusa; Ikeda, Atsuo; Matsumoto, Yoshifumi; Omura, Go; Matsumoto, Fumihiko; Yoshimoto, Seiichi
Abstract: Under extreme conditions and in palliative settings, shared decision making with the patient is vital; narrative decisions beyond evidence could be considered. If there is a chance of symptom palliation, extended surgery should not be avoided merely because of the limited life expectancy. Abstract : Under extreme conditions and in palliative settings, shared decision making with the patient is vital; narrative decisions beyond evidence could be considered. If there is a chance of symptom palliation, extended surgery should not be avoided merely because of the limited life expectancy.